Implementation of Religious Moderation on "MUI Lampung" Youtube Channel - Ermawati, Erda; Mustofa, Muhamad Bisri; Wuryan, Siti; Putri, Ocha Nasria (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
Social media use has increased significantly in recent years, including the YouTube platform. The phenomenon allows religious organizations such as the Lampung Province Indonesian Ulema Council (MUI) to convey religious messages to the wider community. There are various understandings, approaches, and different interpretations of Islamic teachings. This diversity often results in division and tension, increasing the potential for intolerance and radicalism. This article is qualitatively descriptive in analyzing the implementation of religious moderation on the â€œMUI Lampungâ€ YouTube channel; how MUI Lampung constructed lectures on religious moderation from March 2020 to September 2021. This research aims to discover, describe, and analyze the content of religious moderation da'wah conducted by MUI Lampung using Teun A. Van Dijk's discourse analysis. The conclusions of this study are: (1) Lampung MUI packages da'wah videos by inserting the notion of moderation; (2) in each content of its YouTube channel, MUI Lampung provides support to the government in applying moderation to the community; (3) the affiliation of organizational power in conveying moderation discourse influences the ulema in conveying his da'wah.